Rasch analysis of The Melbourne Assessment of Unilateral Upper Limb Function. (5th February 2014) - Randall, Melinda; Imms, Christine; Carey, Leeanne M; Pallant, Julie F
Abstract : Aim: This study investigated the internal construct validity and dimensionality of the Melbourne Assessment of Unilateral Upper Limb Function (Melbourne Assessment), a widely‐used measure of quality of upper limb movement, valid for children aged 2 years 6 months to 15 years with cerebral palsy. Method: Rasch analysis was used to assess of Melbourne Assessment raw scores for 163 children (94 males, 69 females; mean age 8y, SD 3y 5mo). Analysis was undertaken on the full scale comprising 37 scores and on groups of scores separated into four distinct movement subscales: range of movement, accuracy, dexterity, and fluency. Tests were conducted to evaluate overall model fit, item fit, suitability of the response options, unidimensionality, and differential item functioning (DIF) for sex, child age, and different raters. Results: The results did not support the unidimensionality of the 37‐ score scale. The four subscales showed adequate model fit after removal of some score items, and rescaling of others. The resulting subscales showed good internal consistency and no DIF for sex or child age. Interpretation: This study provides empirical support for a revised version of the Melbourne Assessment which comprises 14 tasks and 30 movement scores grouped across four separate subscales. Further testing is required to assess the responsiveness of subscales to clinically important change. What this paper adds: Rasch analysis provided support for a revised version of the Melbourne Assessment (Melbourne Assessment 2) The Melbourne Assessment 2 comprises four distinct subscales: range, accuracy, fluency and dexterity. Each subscale shows fit to the Rasch model and high internal consistency Principal components analysis findings support the unidimensionality of each subscale. This article is commented on by Wallen on pages608–609 of this issue.